COVID-19 Pandemic's Effects on Occupational Health and Perceived Work Ability of a Large Group of Italian Banking Employees - Mendola, Marco; Leoni, Marco; Marano, Giuseppe; Coggiola, Maurizio; Russignaga, Dario; Biganzoli, Elia; Carrer, Paolo (La Medicina del Lavoro, 2024)
Background: The COVID-19 pandemic compelled changes to the structure and organization of many occupational sectors that may impact workers' well-being and work-related symptoms. Objective: Evaluate the effects of working modifications related to the COVID-19 pandemic on occupational health outcomes and work ability (WA) among a large group of Italian banking employees. Methods: 2,859 employees visited during health surveillance in 2021 were divided into two job groups: front-office (FO) and back-office workers (BO). Data on conditions associated with office work, psychological distress, WA, and fitness-to-work judgment were analyzed and compared with available data from the pre-pandemic period (2018–2019). Results: The prevalence of analyzed outcomes was lower than in pre- and post-COVID evaluation literature. After COVID-19, a 28% increase in asthenopin was found in BO, while musculoskeletal symptoms increased about 22% in BO and 9% in FO. Post-COVID showed a 28% rise in stress-related symptoms and a 17% increase in psychotropic drug consumption in both groups. After the lockdown, the prevalence of moderate/poor scores decreased by 13% in each group. Fitness-to-work judgment without limitations prevalence was unchanged. Conclusion: The slight worsening in all examined outcomes at post-lockdown evaluation and the outcomes' prevalence consistently lower than the literature data could be linked to the measures the Institute took to support employees during the COVID-19 pandemic. In this context, a comprehensive integration between occupational safety and health promotion practices is recommended to ensure the highest level of safeguarding for workers' well-being.